Pendekatan Said Nursi terhadap Hadis Daif dalam Karya ‎Risalah Annur: The Approach of Said Nursi Towards Weak (Daif) Hadiths in ‎the Risale-i Nur Collection - Rahim, Nur Aina Mardhiah Che; Musa, Nik Yusri; Zulkifli, Abdul Hayyi; Musa, Shahnun Haji (RABBANICA - Journal of Revealed Knowledge, 2025)
The Risalah An-Nur is a compilation of thoughts by the prominent Turkish Islamic scholar and thinker,Said Nursi. The life challenges he faced span two distinct phases: “Old Said,” which is associated with his direct involvement in political affairs during the rule of Mustafa Kemal Atatürk, and “New Said,” marking a turning point in his outlook where he shifted focus toward writing the Risalah An-Nur. This article aims to examine how Said Nursi interacted with weak (da'if) hadiths in his writings by analysing the principles and criteria he applied in their use. This study employs a library-based methodology, focusing on selected texts within the Risalah An-Nur that contain weak (da'if) hadiths and comparing them with authoritative hadith compilations from Ahl al-Sunnah wa al-Jama‘ah to establish a foundation for his usage. The findings indicate that Said Nursi did not entirely reject weak (da'if) hadiths; instead, he employed them particularly in the context of virtues of deeds (faḍā'il al-a‘māl), in line with the stance of the majority of scholars (jumhūr ‘ulamā’). He used such hadiths to reinforce moral and spiritual messages, but not as binding legal evidence. In several instances, Said Nursi cited hadiths without mentioning their classification, yet the contextual usage suggests that he was aware of their level of authenticity. His focus was on the spiritual messages embedded in the hadiths, considering their educational and transformative impact on the soul, despite the hadiths being weak in terms of chain of narration (sanad). This study concludes with a reflection on Said Nursi’s contribution to contemporary Islamic thought, particularly in enriching the discourse on the role and priority of hadith in the life of the Muslim community. Risalah Annur merupakan garapan dari pemikiran tokoh seorang ulama dan pemikir Islam terkemuka dari Turki iaitu Said Nursi. Cabaran dalam hidup yang beliau hadapi melalui dua dimensi kehidupan berbeza, iaitu Said Lama yang dikaitkan penglibatannya secara langsung dalam kerajaan pada era pemerintahan Mustafa Kamal ATaturk dan Said Baru iaitu titik pertukaran pendangannya ke dunia penulisan kitab Risalah Annur. Artikel ini bertujuan untuk mengupas bagaimana Said Nursi berinteraksi dengan hadis daif dalam karyanya, iaitu dengan menganalisis prinsip dan kriteria penggunaan hadis daif tersebut. Kajian ini menggunakan metode kajian kepustakaan, dengan menumpukan kepada analisis beberapa kitab Risalah Annur yang mengandungi hadis daif dan kitab-kitab hadis dari Ahlu Sunnah wal Jemaah untuk menjadi asas kepada penggunaan hadis daif. Hasil kajian mendapati Said Nursi dilihat tidak menolak hadis daif secara total, sebaliknya menggunakannya dalam konteks fadhail al-a‘mal (kelebihan amalan), selaras dengan pandangan jumhur ulama. Beliau menggunakan hadis daif sebagai penguat dalam menyampaikan mesej moral dan rohani namun tidak menjadikannya sebagai dasar hukum yang mengikat. Dalam beberapa tempat, beliau menukil hadis tanpa menjelaskan statusnya tetapi pemilihan konteks menunjukkan bahawa beliau memahami batas autoritatif hadis tersebut. Said Nursi memberikan penekanan kepada mesej spiritual yang terkandung dalam hadis, dengan mengambil kira kesan didikan kepada jiwa walaupun hadis itu daif dari sudut sanad. Kajian ini diakhiri dengan refleksi terhadap sumbangan Nursi dalam pemikiran Islam kontemporeri, khususnya dalam memperkayakan wacana tentang keutamaan hadis dalam kehidupan umat Islam.